Compatibility and thermal decomposition mechanism of nitrocellulose/Cr2O3 nanoparticles studied using DSC and TG-FTIR. Issue 7 (29th January 2019) - Guo, Yu; Zhao, Ningning; Zhang, Ting; Gong, Hujun; Ma, Haixia; An, Ting; Zhao, Fengqi; Hu, Rongzu
Abstract : Cr2 O3 have good compatibility with nitrocellulose and catalyze decomposition of NC through decrease the activation energy. The mechanism showed Cr2 O3 can accelerate the O–NO2 bond cleavage and speed up the secondary reaction. Abstract : Nano metal oxides are common combustion catalysts for enhancing the burning rate of solid propellants. Cr2 O3 nanoparticles (NPs) are efficient combustion catalysts for the pyrolysis of energetic components. In this study, Cr2 O3 NPs were synthesized via a modified sol–gel method and further used for studying the thermal decomposition of nitrocellulose (NC). Differential scanning calorimetry (DSC) and thermogravimetry-Fourier-transform infrared spectroscopy (TG-FTIR) analyses indicate that the Cr2 O3 NPs can be safely used with NC and the mechanism of the reaction between Cr2 O3 /NC and pure NC follows the Avrami–Erofeev equation: f ( α ) = 3(1 − α )[−ln(1 − α )] 1/3 /2. The peak temperature and activation energy ( E a ) for the thermal decomposition of Cr2 O3 /NC are lower than those of pure NC. NO2 was detected at a lower temperature after NC was mixed with Cr2 O3 NPs; this indicated the catalytically accelerated bond cleavage of NC by Cr2 O3 NPs.